The influence of corporate governance on relational capital disclosure among high growth technology companies / Norman Mohd Saleh and Saiful Bakhtiar Masduki - Mohd Saleh, Norman; Masduki, Saiful Bakhtiar (Universiti Teknologi MARA Cawangan Selangor, 2016)
This study examines the relationship between corporate governance elements and relational capital disclosure. This study analyses 229 annual reports of companies in the technology industry that are listed on the Main and ACE Market of Bursa Malaysia. The results indicate that multiple directorships, institutional and government ownerships positively affect relational capital disclosure. Managerial ownership, on the other hand, reduces the incentives of the management to signal such information. In addition, we also find younger companies to have more incentives to disclose relational capital information compared to more established companies. Contrary from past research, this study used a conceptual model developed based on network theory that suggests companies have an incentive to increase their competitive advantage by increasing network between organizations. This study is the first of its kind that specifically investigates the association between relational capital disclosures with the corporate governance practices. The results highlight that important corporate governance determinants of relational capital disclosure can be predicted when signaling intention of the board and network arguments are considered. The findings are useful for regulators in emerging countries characterized by highly networked economy, whereby, business and personal networks are important for company sustainability.